Effect of a fourth Haemophilus influenzae type b immunisation in preterm infants who received dexamethasone for chronic lung disease. Issue 1 (1st January 2003) - Clarke, P; Powell, P J; Goldblatt, D; Robinson, M J
Abstract : Aim: To assess whether a fourth Hib polysaccharide-tetanus protein conjugate vaccine (PRP-T) would improve antibody response in preterm infants previously treated with dexamethasone for chronic lung disease. Methods: In a pilot study 12 infants born at less than 30 weeks gestation who had received corticosteroids were given a supplementary Hib dose six weeks after completion of the primary immunisation course. Serum samples obtained before and at eight weeks following the fourth Hib dose were analysed for total level and avidity of anti-PRP antibody. Results: There was no significant increase in the geometric mean titre (GMT) of anti-PRP antibody resulting from the fourth Hib immunisation (GMT: pre 2.35 μg/ml, post 2.24 μg/ml, p = 0.79). A subgroup of six infants had subprotective antibody levels (<1.0 μg/ml) after the primary immunisation course, which remained subprotective following the extra Hib immunisation. Despite the poor response in total antibody level, the study group showed a significant rise in PRP specific IgG avidity following the fourth immunisation (GMAI: pre 0.076, post 0.138, p = 0.043). Conclusion: An additional Hib immunisation given to recently steroid treated preterm infants six weeks after completion of the primary schedule did not augment primary immunogenicity. However, increasing avidity may imply successful priming and long term immunity to Hib.